Genetic relationships among Arachis hypogaea L. (AABB) and diploid Arachis species with AA and BB genomes - da Cunha, Fanley Bertoti [UNESP]; Nobile, Paula Macedo; Hoshino, Andrea Akemi [UNESP]; Moretzsohn, Marcio de Carvalho; Lopes, Catalina Romero [UNESP]; Gimenes, Marcos Aparecido [UNESP] (Springer, 2008)
The cultivated peanut (Arachis hypogaea L.) is an allotetraploid, with two types of genomes, classified as AA and BB, according to cytogenetic characters. Similar genomes to those of A. hypogaea are found in the wild diploid species of section Arachis, which is one of the nine Arachis sections. The wild species have resistances to pests and diseases that affect the cultivated peanut and are a potential source of genes to increase the resistance levels in peanut. The aim of this study was to analyze the genetic variability within AA and BB genome species and to evaluate how they are related to each other and to A. hypogaea, using RAPD markers. Eighty-seven polymorphic bands amplified by ten 10-mer primers were analyzed. The species were divided into two major groups, and the AA and the BB genome species were, in general, separated from each other. The results showed that high variation is available within species that have genomes similar to the AA and the BB genomes of A. hypogaea.
Keywords: Arachis hypogaea; genetic variability; peanut; RAPD; wild species